Simple, low-cost, sensitive and label-free aptasensor for the detection of cardiac troponin I based on a gold nanoparticles modified titanium foil - Lopa, Nasrin Siraj; Rahman, Md. Mahbubur; Ahmed, Faiz; Ryu, Taewook; Sutradhar, Sabuj Chandra; Lei, Jin; Kim, Jaewoong; Kim, Dae Ho; Lee, Yong Hoon; Kim, Whangi (Biosensors & bioelectronics, 2019)
This research demonstrated the electrochemical modification of low-cost titanium (Ti) metal substrate with gold nanoparticles (AuNPs) for the aptamer-based detection of cardiac troponin I (cTnI). AuNPs were deposited onto Ti sheets by the potential-step deposition method with high density and homogeneity as well as good crystallinity. It was then applied as a transducer to immobilize a thiol-functionalized DNA aptamer via the self-assembled monolayer mechanism for the specific binding of cTnI. This was verified through electrochemical and morphological analyses. The aptasensor could detect cTnI in a linear range of 1–1100 pM with a detection limit of ca. 0.18 pM. The aptasensor showed high sensitivity and specificity to cTnI over other interfering compounds with good recoveries in the diluted human serum samples. [Display omitted] •AuNPs modified Ti foil is prepared for the aptamer-based detection of cTnI.•High-density AuNPs allows maximizing the immobilization of cTnI-binding aptamers.•The oxidation signal variation of [Fe(CN)6]3-/4- with [cTnI] enables to detect cTnI.•This simple and low-cost aptasensor shows good analytical performance.